Cerebral faith and faith in praxis in the churches of European origin: The Presbyterian Church of South(ern) Africa - Duncan, Graham (HTS teologiese studies, 2023)
This article investigated the paradox between church response to apartheid and resulting action at the local level in the South African churches of European origin from the perspective of the Presbyterian Church of South(ern) Africa (PCSA). It indicated that this discrepancy arose between the reflections (cerebral faith) at the highest levels of church councils, which operated in an intermittent manner and at a distance, compared with the responses (praxis as faith in action) of local church members who lived at the coalface of the struggle and sought to witness in a society dominated by racism, where the tension between faith and politics was most evident. The primary focus was on two inter-racial congregations, one of the PCSA, the other a united congregation in which the PCSA participated. This study used primary and secondary sources. The theoretical framework of the article was Thomas Groome’s approach of shared praxis.Contribution: This article contributed to the history of the apartheid era in ecclesiastical contexts. It demonstrated the anomalies that arose within different constituencies within churches of European origin by investigating the situation in one particular denomination. This was a discussion of the relationship of faith and politics in the private and public domains, which takes account of developments within a shared praxis approach.